Repeat Adverse Drug Reaction-Related Hospital Admissions in Elderly Australians: A Retrospective Study at the Royal Hobart Hospital - Parameswaran Nair, N.; Stafford, Leanne; Bereznicki, B.; Curtain, C.; Bereznicki, L. (Adis International Ltd., 2017)
© 2017, Springer International Publishing AG. Background: Adverse drug reactions are a major cause of hospital admissions in older individuals, with the majority potentially preventable. Despite the apparent magnitude of this problem, little is known about rates of repeat admission to hospital as a result of adverse drug reactions. Objectives: The objectives of this study were to investigate the occurrence of repeat adverse drug reaction-related hospital admissions in elderly patients within 12 months of an adverse drug reaction-related admission to a medical ward and whether a validated adverse drug reaction score could be useful in identifying patients at higher risk of a repeat adverse drug reaction-related hospitalisation. Methods: This retrospective study followed elderly participants who were hospitalised with an adverse drug reaction from our earlier study [the PADR-EC (Prediction of Hospitalization due to Adverse Drug Reactions in Elderly Community-Dwelling Patients) study] to identify repeat adverse drug reaction-related hospital admissions within 12 months of discharge. The PADR-EC score is the sum of points assigned to five significant predictors of adverse drug reaction-related hospitalisation: antihypertensive use, renal failure, dementia, inappropriate anticholinergic use and drug changes in the preceding 3 months. The causality, preventability and severity of each adverse drug reaction-related repeat admission within the 12-month follow-up were assessed. Results: Adverse drug reaction-related repeat admissions occurred after 13.4% (n = 15) of 112 adverse drug reaction-related index admissions. Patients with a repeat adverse drug reaction-related admission had significantly higher PADR-EC scores at discharge of their index admission (median PADR-EC score 7, interquartile range 7–9) than patients who were not readmitted (median PADR-EC score 7, interquartile range 5–7, p = 0.034). Most (73.3%) adverse drug reaction-related repeat admissions were considered ‘preventable’. Adverse drug reaction severity was ‘moderate’ in all cases. Renal disorders (44.4%) represented the most common adverse drug reactions and the most frequently implicated drug classes were diuretics (44.8%). All adverse drug reaction-related repeat admissions were found to be ‘probable’. Conclusions: One in eight elderly patients hospitalised because of an adverse drug reaction had a repeat admission for an adverse drug reaction within 12 months of discharge. The PADR-EC score could potentially be used at hospital discharge to prioritise patients for interventions to prevent subsequent adverse drug reaction-related hospital admissions.